2014
DOI: 10.1016/j.envpol.2014.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and transport of 17 perfluoroalkyl acids in 12 coastal rivers in south Bohai coastal region of China with concentrated fluoropolymer facilities

Abstract: a b s t r a c tPerfluoroalkyl acids (PFAAs) are emerging contaminants that have raised great concern in recent years. While PFAAs manufacturing becomes regulated in developed countries, production has been partly shifted to China. Eight fluoropolymer manufacturing facilities located in the South Bohai coastal region, one of the most populated areas of China, have been used to manufacture PFAA-related substances since 2001. The environmental consequence of the intensive production of PFAAs in this region remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
82
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 148 publications
(93 citation statements)
references
References 45 publications
11
82
0
Order By: Relevance
“…Water samples (400 mL) were extracted using OASIS WAX-SPE according to previously described method with minor modifications (Wang et al 2014a). Before water sample loading, 10-ng mass-labeled internal standards were spiked into samples and thoroughly mixed.…”
Section: Sampling Campaignmentioning
confidence: 99%
“…Water samples (400 mL) were extracted using OASIS WAX-SPE according to previously described method with minor modifications (Wang et al 2014a). Before water sample loading, 10-ng mass-labeled internal standards were spiked into samples and thoroughly mixed.…”
Section: Sampling Campaignmentioning
confidence: 99%
“…Hundreds of rivers in China as well as in the Korean Peninsula discharge industrial and domestic wastewater into this region (Jin et al, 2015;Kim, 2012;P. Wang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al, 2014). In the semiclosed Bohai Sea, high concentrations of PFOA and PFOS were detected in the rivers emptying into the sea, which may have elevated the levels of PFOA and PFOS in the seawater (Sun et al, 2011;P. Wang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Perfluorooctanoic acid (PFOA), another highly investigated PFAA, is due to be phased out in the USA following agreements with industry in that country by (USEPA, 2006. There has been a trend for the manufacture of PFAAs and fluoro-polymers/-telomers to shift from North America and Europe to emerging economies, especially China (Wang et al, 2014a;Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have found an important point source of PFAAs, a mega fluorochemical industrial park (FIP), in the Xiaoqing River basin in northern China (Wang et al, 2014a). PFAAs levels up to 1.06 mg/L, with a mass load of 174 kg/d, were identified at downstream of the FIP (Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%